Nanocontact printing stamp material via bi-functionalization of polyhedral oligomeric silsesquioxanes. (April 2015) - Kastner, Julia; Lorret, Olivier; Rank, Andreas; Schwarzinger, Clemens; Dittert, Bernd; Mühlberger, Michael
Graphical abstract: Highlights: Synthesis and characterization of bi-functionalized polyhedral oligomeric silsesquioxane. Application of bi-functional POSS as stamp material for nanocontact printing. Improved resolution obtained using POSS as alternative for PDMS stamp. Deposition of protein patterns with 50 nm lines described. Abstract: Microcontact printing (μCP) is a widely used technique for depositing proteins in micro patterns. The investigation of protein–protein interactions in small cells like T-cells (5–10 μm), however, require feature sizes in the nanometer range which could be created by nanocontact printing (nCP). The main intention of our work was to develop functionalized Polyhedral Oligomeric Silsesquioxane (POSS) materials as an alternative for poly(dimethylsiloxane) (PDMS) which are commonly used as stamp material for micro-contact printing. POSS materials combine many desirable properties of conventional organic and inorganic components and provide an exemplary core system for developing versatile functional resist materials. Their properties are easily tunable by molecular design to suit the desired application. Used as stamp material POSS combines the advantages of hard stamps for high resolution printing and the possibility to tune the surface chemistry to enable a proper transfer of proteins. In this work, epoxy as well as carboxylic acid functionalized POSS were synthesized and epoxy–carboxylic acid bi-functionalized POSS materials have been developed for nCP stamp applications. The POSS polymers were designed by incorporating the necessary functional groups onto the silsesquioxane cage via platinum catalyzed hydrosilylation chemistry. The presence of epoxy groups allows the resists to polymerize at room temperature under UV-light exposure, while carboxylic acid groups ensure the presence of anionic species (COO − ) at the surface of the stamps to facilitate protein transfer. The as-synthesized materials were characterized and supposed structures of the cured materials were confirmed by spectroscopic methods. Via nCP a monolayer of nanoscale avidin patterns have been deposited on epoxy-functionalized glass substrates.